A two-sample Mendelian randomization analysis: causal association between chemokines and pan-carcinoma - Cui, Kai; Song, Na; Fan, Yanwu; Zeng, Liqun; Shi, Pingyu; Wang, Ziwei; Su, Wei; Wang, Haijun (Frontiers in Genetics, 2023)
According to the 2020 data from the World Health Organization (WHO), cancers stand as one of the foremost contributors to global mortality. Revealing novel cancer risk factors and protective factors is of paramount importance in the prevention of disease occurrence. Studies on the relationship between chemokines and cancer are ongoing; however, due to the coordination of multiple potential mechanisms, the specific causal association remains unclear.Methods: We performed a bidirectional Mendelian randomization analysis to explore the causal association between serum chemokines and pan-carcinoma. All data is from the GWAS catalog and IEU Open GWAS database. The inverse variance weighting (IVW) method is primarily employed for assessing the statistical significance of the findings. In addition, the significance threshold after the multiple hypothesis test (Bonferroni) was 0.0013, and the evidence of a potential association was considered if the p-value < 0.05, but remained greater than Bonferroni's threshold.The results indicate that CCL1 (odds ratio, OR = 1.18), CCL2 (OR = 1.04),